The impact of Facebook Addiction and self-esteem on students' academic performance: A multi-group analysis. (December 2019) - Busalim, Abdelsalam H.; Masrom, Maslin; Binti Wan Zakaria, Wan Normeza
Abstract: As Facebook is still the most popular online social network, several studies confirm that the excessive use of Facebook leads to addictive behavior, especially among the younger generation. This study aims to explore the effect of Facebook addiction, and self-esteem on students' academic performance. Using the Bergen Facebook Addiction Scale, and Rosenberg's Self-Esteem scale, online survey was developed to collect data from one public university in Malaysia. A total of n = 240 students participated in the study. The results of the study revealed that addicted students differ statistically in self-esteem from non-addicted students. Moreover, the results showed that Facebook addiction has significant effect on students' academic performance for both samples, and frequency of Facebook use also was found to be a positive predictor of Facebook addiction. The findings of the study provide empirical evidences for the effect of Facebook addiction on students' academic performance. The results also provide a better understanding of self-esteem factor that significantly effect on student's Facebook addiction and academic performance. Highlights: Multi-group analysis was used to test the significant differences between addicted and non-addicted students. Self-esteem has negative significant impact on Facebook addiction for non-addicted students. Self-esteem found to be a positive predictor of students' academic performance for non-addicted students. Facebook Frequency of use has a direct positive influence on students Facebook addiction. Facebook addiction has negative effect on the decline of students' academic performance for both samples.